Daytime and Nighttime Sleep Characteristics and Pain Among Adults With Stable Heart Failure. Issue 5 (September 2019) - Conley, Samantha; Feder, Shelli L.; Jeon, Sangchoon; Redeker, Nancy S.
Abstract : Background: Pain and sleep disturbance are common among patients with heart failure (HF) and are associated with symptom burden, disability, and poor quality of life. Little is known about the associations between specific sleep characteristics and pain in people with HF. Objective: The aim of this study was to describe the relationships between nocturnal sleep characteristics, use of sleep medication, and daytime sleep characteristics and pain among people with HF. Methods: We conducted a cross-sectional study of stable participants with HF. We administered the SF36 Bodily Pain Scale, Pittsburgh Sleep Quality Index, and Sleep Habits Questionnaire and obtained 3 days of wrist actigraphy and 1 night of home unattended polysomnography. We conducted bivariate analyses and generalized linear models. Results: The sample included 173 participants (mean [SD] age, 60 [16.1] years; 65.3% [n = 113] male). Insomnia symptoms ( P = .0010), sleep duration ( P = .0010), poor sleep quality ( P = .0153), use of sleep medications ( P = .0170), napping ( P = .0029), and daytime sleepiness ( P = .0094) were associated with increased pain. Patients with the longest sleep duration, who also had insomnia, had more pain ( P = .0004), fatigue ( P = .0028), daytime sleepiness ( P = .0136), and poorer sleep quality ( P < .0001) and took more sleep medications ( P = .0029) than did those without insomnia. Conclusions: Pain is associated with self-reported poor sleep quality, napping, daytime sleepiness, and use of sleep medication. The relationship between pain and sleep characteristics differs based on the presence of insomnia and sleep duration. Studies are needed to evaluate the causal relationships between sleep and pain and test interventions for these cooccurring symptoms.